2004
DOI: 10.1002/biof.5520220128
|View full text |Cite
|
Sign up to set email alerts
|

Concord grape juice supplementation reduces blood pressure in Korean hypertensive men: Double‐blind, placebo controlled intervention trial

Abstract: Many of the flavonoids found in grapes and grape products such as juice or wine have been known to exert antioxidant, anti-inflammatory, platelet inhibitory and arterial relaxing effects either in vitro, in animal studies and in human trials. This study was designed to test the effect of Concord grape juice consumption on altering blood pressure in hypertensive patients. Forty subjects were given 5.5 ml/kg body weight/day of either Concord grape juice (CGJ) or a calorie-matched placebo drink every day for 8 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 6 publications
5
72
0
2
Order By: Relevance
“…Also, grape polyphenols may have a reducing effect in cardiac fibrosis, a process occurring in cases of hypertension (17) Thirty-five healthy women 4 weeks Red wine with 13·5 % ethanol and 1·9 g total polyphenols/l or white wine with 13 % ethanol and 0·31 g total polyphenols/l Agewall et al (2000) (18) Twelve healthy subjects Acute intake Red wine with 1·9 g total polyphenols/l and 12·5 % ethanol or dealcoholised red wine with 1·1 g total polyphenols/l (250 ml in all groups) Cross-over design Naissides et al (2004) (19) Seventeen postmenopausal women Acute intake Dealcoholised red wine with 2·2 g total polyphenols/l, white wine with 2·2 g total polyphenols/l or water Cross-over design Williams et al (2004) (20) Fourteen men with stable IHD Acute intake Red wine with 13·5 % ethanol and 1·2 g total polyphenols/l, white wine with 13 % ethanol and 0·2 g total polyphenols/l or non-alcoholic drink without polyphenols Cross-over design Pignatelli et al (2006) (21) Twenty healthy subjects 3 weeks Red wine with 12·5 % ethanol and 1·2 g total polyphenols/l or white wine with 12·5 % ethanol and 0·18 g total polyphenols/l Castilla et al (2008) (24) Thirty-two haemodialysed patients 2 weeks Red grape concentrate (100 ml/d ¼ 600 mg total polyphenols/d), 800 IU (20 mg) vitamin E/d or both De Rijke et al (1996) (25) Twenty-four healthy subjects 2 weeks, then 4 weeks with different treatments (33) Nine hypercholesterolaemic and eight normocholesterolaemic subjects (45) Hypertensive men 8 weeks Grape juice with 2·1 g total polyphenols/l or placebo (11 ml/kg weight per d in all groups) Ward et al (2005) (46) Hypertensive subjects 6 weeks Vitamin C, polyphenols from red grape seeds (1 g/d), both or control Chou et al (2001) (47) Fifteen healthy subjects 1 week Extract from grape peel with 5 % total polyphenols (600 mg extract/d) Matsuo et al (2001) (51) Six men Acute intake Red wine, ethanol, polyphenols from red wine Cross-over design Freedman et al (2001) (52) Twenty healthy volunteers 2 weeks Purple grape juice (7 ml/kg weight per d) Boban et al (2006) (53) Nine men Acute intake Red wine, dealcoholised red wine, polyphenols from red wine, ethanol -water solution, water Cross-over design Whelan et al (2004) (10...…”
Section: Effects On Blood Pressure: Endothelial Functionmentioning
confidence: 99%
“…Also, grape polyphenols may have a reducing effect in cardiac fibrosis, a process occurring in cases of hypertension (17) Thirty-five healthy women 4 weeks Red wine with 13·5 % ethanol and 1·9 g total polyphenols/l or white wine with 13 % ethanol and 0·31 g total polyphenols/l Agewall et al (2000) (18) Twelve healthy subjects Acute intake Red wine with 1·9 g total polyphenols/l and 12·5 % ethanol or dealcoholised red wine with 1·1 g total polyphenols/l (250 ml in all groups) Cross-over design Naissides et al (2004) (19) Seventeen postmenopausal women Acute intake Dealcoholised red wine with 2·2 g total polyphenols/l, white wine with 2·2 g total polyphenols/l or water Cross-over design Williams et al (2004) (20) Fourteen men with stable IHD Acute intake Red wine with 13·5 % ethanol and 1·2 g total polyphenols/l, white wine with 13 % ethanol and 0·2 g total polyphenols/l or non-alcoholic drink without polyphenols Cross-over design Pignatelli et al (2006) (21) Twenty healthy subjects 3 weeks Red wine with 12·5 % ethanol and 1·2 g total polyphenols/l or white wine with 12·5 % ethanol and 0·18 g total polyphenols/l Castilla et al (2008) (24) Thirty-two haemodialysed patients 2 weeks Red grape concentrate (100 ml/d ¼ 600 mg total polyphenols/d), 800 IU (20 mg) vitamin E/d or both De Rijke et al (1996) (25) Twenty-four healthy subjects 2 weeks, then 4 weeks with different treatments (33) Nine hypercholesterolaemic and eight normocholesterolaemic subjects (45) Hypertensive men 8 weeks Grape juice with 2·1 g total polyphenols/l or placebo (11 ml/kg weight per d in all groups) Ward et al (2005) (46) Hypertensive subjects 6 weeks Vitamin C, polyphenols from red grape seeds (1 g/d), both or control Chou et al (2001) (47) Fifteen healthy subjects 1 week Extract from grape peel with 5 % total polyphenols (600 mg extract/d) Matsuo et al (2001) (51) Six men Acute intake Red wine, ethanol, polyphenols from red wine Cross-over design Freedman et al (2001) (52) Twenty healthy volunteers 2 weeks Purple grape juice (7 ml/kg weight per d) Boban et al (2006) (53) Nine men Acute intake Red wine, dealcoholised red wine, polyphenols from red wine, ethanol -water solution, water Cross-over design Whelan et al (2004) (10...…”
Section: Effects On Blood Pressure: Endothelial Functionmentioning
confidence: 99%
“…Its important to note that the consumption of grape juice in the study of Park et al [36] gave an average 881.14 mg/day of flavonoids, whereas in these studies from isolated nutrients it was 500 mg [26][27][28]. This corroborates the ability of grape juice (being consumed daily around 425.6 mL) to promote beneficial effects on blood pressure and great applicability to the general population.…”
Section: Foods In Naturementioning
confidence: 55%
“…Among the studies selected in this paper, we have investigated the effects of garlic [34], grape juice [36], and whey [35], all in hypertensive middle-aged people. While the wine had been well investigated, this paper found only studies with normotensive, which was an exclusion criterion at the time of selection of papers.…”
Section: Foods In Naturementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in studies conducted with grapes and grape juice, clinical trials have demonstrated decreased platelet aggregation (PaceAsciak et al, 1996;Folts, 1998;Keevil et al, 2000;Freedman et al, 2001), improved endothelial function (Stein et al, 1999;Coimbra et al, 2005;Lekakis et al, 2005), reduced blood pressure (Park et al, 2004), and positive influences on biomarkers such as HDL, LDL, apo-B, and MCP-1 (Hansen et al, 2005;Zern et al, 2005;Castilla et al, 2006). Accordingly, it is apparent that grape consumption can modulate several factors that are associated with health benefits.…”
Section: Introductionmentioning
confidence: 99%